ORAI2 modulates store-operated calcium entry and T cell-mediated immunity - Martin Vaeth (Nature Portfolio, 2017)
Ca2+ release-activated Ca2+(CRAC) channels are essential for protective immunity, but the immunological functions of the three ORAI homologues that form CRAC channels are unclear. Here the authors show that ORAI1 and ORAI2 form heteromeric CRAC channels, which fine-tune T cell activation and immune responses.